Pemertahanan Bahasa Sindang pada Masyarakat Kota Lubuklinggau - Nur Nisai Muslihah; Rusmana Dewi; Lessy Puspitasari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
This research aims at describing the maintenance of Sindang language in Watervang subdistrict Lubuklinggau city which was focused on the maintenance of Sindang language in teenagers and adults domain. The research was a quantitative descriptive research with 59 informants of teenagers and adults. The data collection was conducted through closed questionnaire. The data were analyzed by using percentage calculation. The results showed that the maintenance of Sindang language on teenagers group was 73,01 with 'good'category, and on adults group was 80,57 with 'good' category. Based on the average calculation, it can be concluded that the attitude of the language maintenance on Sindang language among teenagers and adults in Watervang subdistrict Lubuklinggau city is in 'good' criteria. Keywords: Maintenance, Sindang Language, Watervang Subdistrict